Witherwood Reform School - Skye, Obert (Skye, Obert. Witherwood Reform School, 2016)
When siblings Charlotte and Tobias are sent to Witherwood, a spooky reform school, they become entangled in its dark secrets and race to save themselves and the children trapped there.